Studi Pemikiran Pendidikan menurut Ki Hajar Dewantoro - Khoir, Mulyanto Abdul; Fahriani, Aulia Nurul; Amriati, Ulil (TSAQOFAH, 2026)
Ki Hajar Dewantara’s educational thought has made a fundamental contribution to shaping Indonesia’s national education system; however, studies that systematically elaborate his educational concepts from the nature and aims of education to the role of the educator and their relevance to contemporary education remain limited. This article aims to examine in depth Ki Hajar Dewantara’s concept of education, encompassing the nature of education, educational goals, the role of the educator, and its relevance to the dynamics of modern education. The study employs a library research method with a qualitative-descriptive approach to Ki Hajar Dewantara’s works and relevant supporting literature. The findings indicate that Ki Hajar Dewantara’s educational thought emphasizes a humanistic education rooted in national culture and oriented toward the liberation and holistic development of learners’ potential, thereby positioning education as a process of humanization and emancipation. These findings affirm that Ki Hajar Dewantara’s concept of education remains relevant for strengthening character, developing culture, and fostering learner autonomy within the context of contemporary national education, while also providing a philosophical foundation for formulating educational policies and practices that are more just, personality-based, and humanity-oriented.